2019
DOI: 10.1101/809442
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evolutionary impact of size-selective harvesting on shoaling behavior: Individual-level mechanisms and possible consequences for natural and fishing mortality

Abstract: Many fisheries around the globe preferentially capture large individuals with implications for the evolution of exploited populations. Fisheries-induced evolution may alter collective behavioral phenotypes through individual-level adaptations that affect boldness, swimming speed and tendency to follow social vs. environmental cues. Studying the behavioural mechanisms that give rise to possible changes in shoaling and other collective outputs is challenging in the wild, but first insights into whether intensive… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 113 publications
0
7
0
Order By: Relevance
“…A particularly prominent simplification often encountered in models of collective behavior is the assumption of constant speed of individual agents [13,[21][22][23]; for exceptions see [24][25][26][27][28]. However, although animals may generally tend to move at a certain, often preferred, speed, they are also able to flexibly modify their speed, ranging from non-moving to the maximum of their movement capacity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A particularly prominent simplification often encountered in models of collective behavior is the assumption of constant speed of individual agents [13,[21][22][23]; for exceptions see [24][25][26][27][28]. However, although animals may generally tend to move at a certain, often preferred, speed, they are also able to flexibly modify their speed, ranging from non-moving to the maximum of their movement capacity.…”
Section: Introductionmentioning
confidence: 99%
“…These feedbacks incorporate both, the physics and behavioral side of collective behavior. Due to this combination, they have not been explored, to our best knowledge, in the field of 1) active aligning particle models [16,18,33,34], which are often variants of the Vicsek model that either lack inertia, repulsion and/or speed variability (none of those is present in the Vicsek model), 2) active Brownian particles [35] which consider speed variablility and repulsion but operate normally in the over-damped limit (no inertia) and rarely take alignment into account, 3) burst-coast models [26][27][28]36] which model swimming behavior in greater detail (distinct phases of de-and acceleration) but either speeds are picked randomly independent of social interactions and current state [27,36] or the focus was to resemble experimentally observed individual behavior in detail without investigating emergent effects on the collective level [26,28].…”
Section: Introductionmentioning
confidence: 99%
“…This is evidence that five generations of selection left a genetic legacy in our zebrafish population [19], while maintaining basic genetic variability (Uusi-Heikkilä et al, unpublished data). Moreover, recent studies with these lines (using F 13 ) showed differences in behavioural traits related to biological rhythms, feeding and mating [16,59,60]. Associated with the substantial molecular and phenotypic differences among the size-selected lines, we expected the evolution of line-assortative mating preferences and reproductive success.…”
Section: Discussionmentioning
confidence: 85%
“…Females could also exert a preference for bolder males with higher risk-taking tendencies [81,95,96]. Previous studies with the zebrafish lines have indicated that control line fish are bolder than the large-harvested line fish [60,61], and this difference in personality could explain why the former were preferred. Large males have higher reproductive success [39,63] and are more often chosen as mating partners in zebrafish [65,70].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation